2002
DOI: 10.1111/j.1749-6632.2002.tb04074.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide in Liver Diseases

Abstract: Research on the free radical gas, nitric oxide (NO), during the past twenty years is one of the most rapid growing areas in biology. NO seems to play a part in almost every organ and tissue. However, there is considerable controversy and confusion in understanding its role. The liver is one organ that is clearly influenced by NO. Acute versus chronic exposure to NO has been associated with distinct patterns of liver disease. In this paper we review and discuss the involvement of NO in various liver diseases co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(33 citation statements)
references
References 154 publications
1
28
2
1
Order By: Relevance
“…Nitric oxide modifies DNA, proteins, and lipids or interacts with transition metals and free radical residues in a variety of cell types, including macrophages and hepatocytes (8), and participates in processes leading to inflammation and tumorigenesis. In addition to studies suggesting the prominent correlation between high levels of iNOS expression and acute and chronic hepatitis B (21,22), Kane et al (23) have shown that increased levels of nitrate and N-nitroso carcinogenic compounds are associated with DNA mutagenesis in chronic hepatitis C virus infection. Interestingly, NO also mediates the antiviral activity by inhibiting the replication of HBV and lymphocytic choriomeningitis virus (24).…”
mentioning
confidence: 99%
“…Nitric oxide modifies DNA, proteins, and lipids or interacts with transition metals and free radical residues in a variety of cell types, including macrophages and hepatocytes (8), and participates in processes leading to inflammation and tumorigenesis. In addition to studies suggesting the prominent correlation between high levels of iNOS expression and acute and chronic hepatitis B (21,22), Kane et al (23) have shown that increased levels of nitrate and N-nitroso carcinogenic compounds are associated with DNA mutagenesis in chronic hepatitis C virus infection. Interestingly, NO also mediates the antiviral activity by inhibiting the replication of HBV and lymphocytic choriomeningitis virus (24).…”
mentioning
confidence: 99%
“…It has various functional messengers in numerous vertebrates. The liver is an organ that is clearly influenced by NO [46]. Using different models of liver damage, the role of NO in the liver remains controversial and it may be associated with both beneficial and detrimental consequences [47].…”
Section: Discussionmentioning
confidence: 99%
“…During the pre-HCC period, viral infection (hepatitis B and C) or other unforeseen circumstances may lead to uncontrolled, prolonged, and/or massive production of NO by inducible nitric oxide synthase (iNOS) in the liver [6]. At the same time, NO released by the tumor cells might enhance angiogenesis, which can lead to accelerated growth of the primary tumor, as well as facilitate the process of metastasis [6]. …”
Section: Introductionmentioning
confidence: 99%